Using control methods to evaluate the effect of unpinning on the Roi Baudouin Ice shelf, East Antarctica - Favier, Lionel; Mercenier, Rémy R.M; Berger, Sophie; Drews, Reinhard; Witrant, Emmanuel; Pattyn, Frank (2014)
info:eu-repo/semantics/nonPublished